Perceptions about learning graphic design in Journalism university studies in Spain: contents, utility and training level - Suárez Carballo, Fernando; Martín San Román, Juan Ramón (Estudios sobre el Mensaje Periodístico, 2015)
This study aims to examine the situation of graphic design in the Journalism university students training in Spain through the perceptions of professionals and professors specializing in this area. The research tries to evaluate the presence of this field according to three main thematic viewpoints (contents, utility and training level), in order to discover how the abilities offered by these programs respond to the professional requirements. From the analysis of these parameters with a quantitative survey methodology, the article concludes that these studies are insufficient compared to the work demands.